The Use and Risks of Flavoring Agents in Electronic Cigarettes: Toxicological Approach - Çok, İsmet (Addicta: The Turkish Journal on Addictions, 2023)
Because Electronic Nicotine Delivery Systems are fairly new, the information on the health risks of these systems is very limited; however, recent studies have provided results that show the harmful health effects of these products. Studies that have investigated the many chemicals in electronic cigarettes have reported a lesser ratio of harmful compounds in the vapor of e-cigarettes than that from regular cigarettes; however, it is misleading to claim no exposure to chemicals or carcinogens from electronic cigarette use for both the users and the public in terms of potential health risks. In fact, studies have found at least 20 human carcinogens and teratogens in the electronic liquids and vapor from these products. Chemicals used to flavor the products are among the main causes of harmful exposure, and their use is the leading cause of increased use of these products and plays an important role in creating a new epidemic health threat because of the lack of scientific data on the health risks of usage and exposure to various chemicals. The government and regulatory authorities have taken inadequate legal measures to limit the use of flavoring chemicals in these and tobacco products in general, which remains a public concern.